(untitled) (Asian Journal of Medical and Biological Research, 2015)
Peste des petits ruminants (PPR) is a highly contagious viral disease associated with high morbidity and mortality in goats of Bangladesh. Though there is no known effective drug against PPR virus, Animal Health Research Division (AHRD), Bangladesh Livestock Research Institute (BLRI) has developed a treatment technology antibiotic combined hyperimmune serum therapy (ACHST) against the deadly PPR virus. This article described the management of a huge outbreak of PPR by ACHST at goat farm of BLRI regional station, Naikhongchari, Bandarban, a hilly area of Bangladesh. Seventy two goats out of 159 goats were infected with PPR virus naturally. The clinical history and necropsy findings were recorded and nasal swabs were collected for diagnosis of PPR virus by RT-PCR. Thirty goats among 72 goats were died before providing treatment and the rest alive 42 goats were received ACHST. Each of the goats was treated with PPR specific hyperimmune serum @ 4-5ml/goat slow IV for once, Amcicoli-D (Ampicillin trihydrate, Colistin sulfate and Dexamethasone acetate) @ 1ml/10kg body weight daily IM once for 3 days and metronidazole @ 500mg/35kg body weight orally thrice daily for 3 days. After treatment, 38 goats (93.23%) were recovered out of 42 goats. The comparative evaluation of ACHST at different stages of naturally PPR infected goats shown highest recovery rate in incubation (100%) and prodromal (100%) phases followed by pneumonic (91.67%) and diarrhoeal (81.25%) phases. It may be concluded that the ACHST could be used as therapeutic interventions for PPR infected goats. Asian J. Med. Biol. Res. June 2015, 1(2): 230-234